Hypoxia- and Postirradiation reoxygenation-induced HMHA1/ARHGAP45 expression contributes to cancer cell invasion in a HIF-dependent manner - Lee, PWT; Suwa, T; Kobayashi, M; Yang, H; Koseki, LR; Takeuchi, S; Chow, CCT; Yasuhara, T; Harada, H (Springer Nature [academic journals on nature.com], 2024)
Background: Cancer cells in severely hypoxic regions have been reported to invade towards tumour blood vessels after surviving radiotherapy in a postirradiation reoxygenation- and hypoxia-inducible factor (HIF)-dependent manner and cause recurrence. However, how HIF induces invasiveness of irradiated and reoxygenated cancer cells remains unclear. Methods: Here, we identified human minor histocompatibility antigen 1 (HMHA1), which has been suggested to function in cytoskeleton dynamics and cellular motility, as a responsible factor and elucidated its mechanism of action using molecular and cellular biology techniques. Results: HMHA1 expression was found to be induced at the transcription initiation level in a HIF-dependent manner under hypoxia. Boyden chamber invasion assay revealed that the induction of HMHA1 expression is required for the increase in invasion of hypoxic cancer cells. Reoxygenation treatment after ionising radiation in vitro that mimics dynamic changes of a microenvironment in hypoxic regions of tumour tissues after radiation therapy further enhanced HMHA1 expression and invasive potential of HMHA1 wildtype cancer cells in ROS- and HIF-dependent manners, but not of HMHA1 knockout cells. Conclusion: These results together provide insights into a potential molecular mechanism of the acquisition of invasiveness by hypoxic cancer cells after radiotherapy via the activation of the ROS/HIF/HMHA1 axis.